Critical Steady-State Response of Single-Degree-of-Freedom Bilinear Hysteretic System under Multi Impulse as Substitute of Long-Duration Ground Motion - Kojima, Kotaro; Takewaki, Izuru (Frontiers in Built Environment, 2017)
A set of multiple impulses is introduced as a substitute of many-cycle harmonic waves which represent the long-duration earthquake ground motion. A closed-form expression is derived of the elastic-plastic response of a single-degree-of-freedom (SDOF) structure with bilinear hysteresis under the ‘critical multiple impulse input’. As in the case of elastic-perfectly plastic models, an advantageous feature can be used such that only the free-vibration exists under the multiple ground motion impulse and the energy balance approach plays a key role in the derivation of the closed-form expression of a complicated elastic-plastic response. It is demonstrated that the critical inelastic maximum deformation and the corresponding critical impulse timing can be obtained depending on the input level. The validity and accuracy of the proposed theory are confirmed through the comparison with the response analysis to the corresponding sine wave as a representative of the long-duration earthquake ground motion.